AB0744 There is NO Relationship between Glucagon like Peptide-1 and Inflammation in Psoriasis and Psoriatic Arthritis. (10th June 2014) - Keser, M.; Cetin, P.; Solmaz, D.; Kozacı, D.; Gunay, N.; Oztürk, S.; Sarı, I.; Akar, S.; Birlik, M.; Akkoc, N.; Onen, F.
Abstract : Background: Several studies have found a higher prevalence of type 2 diabetes mellitus in patients with psoriasis and psoriatic arthritis (PsA). Interestingly, a complete remission of psoriasis has been observed following immediately after the gastric bypass surgery in obese diabetic patients before any weight loss could have occurred, most likely due to the increased levels of GLP-1. There have been also diabetic cases who have showed improvements in psoriasis under the treatment with GLP-1 receptor agonists and with dipeptidyl peptidase-IV (DPP-IV) inhibitors.GLP-1 was suggested to have anti-inflammatory effects in addition to its effects on glucose homeostasis. Objectives: To investigate the GLP-1 level and its relationship with inflammation in patients with psoriasis and PsA. Methods: This study included non-diabetic PsA patients and healthy controls. Disease activity was assessed in the patients by using "Composite Psoriatic Disease Activity Index (CPDAI)" which assessed five domains of disease: peripheral arthritis, dactylitis, enthesitis, axial involvement and skin findings. High-sensitive C-reactive protein (hs-CRP) levels were also investigated for the assessment of the disease activity. Fasting blood GLP-1 levels were measured in PsA patients by using ELISA method and compared with those measured in the controls. Results: There were 97 PsA patients who fulfilled the CASPAR criteria. Fifty-seven healthy sex, age- and –body mass index (BMI) matched hospital workers were evaluated as controls (Table 1 ).14 patients had predominantly axial and 52 had predominantly peripheral disease. 22 (17.5%) were receiving corticosteroids. 12 patients (7.8%) were on anti-TNF treatment, 78 (%80.4) were on methotrexate.There was no statistically significant difference in the GLP-1 levels between PsA patients and healthy controls. GLP-1 levels in patients with active disease were also not different from inactive patients and controls. No difference was determined in GLP-1 levels between patients with predominantly axial and predominantly peripheral disease and healthy controls. GLP-1 levels in patients with psoriasis and PsA were not correlated with the other disease activity scores including BASDAI, DAS28, PASI and hsCRP levels. There was also no correlation between GLP-1 level and functional disease index (BASFI) and also health assessment parameters (HAQ, ASQoL). The subgroup analysis in patients who were not taking glucocorticoid treatment (n:27) revealed the similar results. Conclusions: The results of this study suggests that there is no significant relationship between GLP-1 and inflammatory process in patients with psoriasis and PsA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4514